A Corpus-Based Cross-Disciplinary Study of Unattended Anaphoric Pronouns in L2 Postgraduate Theses - Kyei, Emmanuel; Esther Serwaah Afreh; Osei Yaw Akoto; Wilson Awiah Jujugenia; Kofi Soadwah (Universitas Kapuas, 2025)
This study examines unattended anaphoric pronouns in postgraduate theses across four academic disciplines (English, Economics, Biology, and Civil Engineering) from a Ghanaian public university, focusing on the period between 1980 and 2022. A corpus-based analysis and the analytical framework from Chang and Swales (1999), adapted by Hyland and Jiang (2017), was adopted to investigate the differences in the occurrence and use of unattended anaphoric pronouns across these disciplines. It also explored the verbs most commonly associated with unattended anaphoric pronouns within the theses. The findings revealed significant discipline-specific patterns in the use of unattended anaphoric pronouns, with distinct preferences in verb usage across English, Economics, Biology, and Civil Engineering. In the analysis of unattended anaphoric pronouns, “this” was the most frequently used across all disciplines, with Economics exhibiting the highest frequency at 15.95 per 10,000 words. The collocational pattern “this is/was” was the most frequently used in the corpora. The study concludes that the academic discipline influences reference strategies, offering insights into the structural and rhetorical features of postgraduate writing in these fields. The study contributes to a deeper understanding of how disciplinary discourse shapes academic writing practices in Ghanaian postgraduate education.